PERANAN WORLD WIDE FUND FOR NATURE (WWF) DALAM UPAYA KONSERVASI POPULASI BADAK JAWA DI INDONESIA - Eca Chairunnisa (Global Political Studies Journal, 2018)
This study is to examine the role of the World Wide Fund for Nature (WWF) in the Javan rhino population conservation efforts in Indonesia. Endangered Javan rhino population makes the WWF as an environmental organization that also address the issue of endangered species, participating in efforts to conserve this species. Researchers analyzed the various efforts made by the WWF conservation of Javan rhino populations in Indonesia so that the species can survive in their habitat. The research method used in this study is the author of qualitative methods, aims to describe the facts relating to the problem under study. Most of the data collected through library research, online data retrieval, documentation, interviews and observations. The data was then analyzed with theoretical approaches associated with theories of International Relations such as the International Organizations Role Theory, and International Cooperation. The results showed that the WWF has done his role as international organizations in dealing with the extinction of the Javan Rhino. Javan rhino population conservation programs that have been carried out by WWF in Indonesia has resulted in an increase in member javan rhino population. Thus, an important role in the conservation of WWF Indonesia's Javan rhino population.